ПРОБЛЕМА КЛАСИФІКАЦІЇ ТОЛЕРАНТНОСТІ В НАУКОВИХ ДОСЛІДЖЕННЯХ - Ляпунова, Валентина (Збірник наукових праць Уманського державного педагогічного університету, 2020)
Стаття присвячена теоретичному огляду наукових доробків щодо класифікації видів толерантності з точки зору різних наук. Розглядаються основні критерії, покладені в основу цих класифікацій. На підставі аналізу позицій різних авторів зроблено висновок про те, що наукові підходи до класифікації толерантності в даний час відрізняються великою строкатістю, неузгодженістю та суперечливістю. Оскільки критерії для узагальнення такої великої кількості емпіричного матеріалу поки не вироблені, доцільною стає розробка єдиного методичного інструментарію, що поєднує в собі всі перераховані види толерантності. Статья посвящена теоретическому обзору научных разработок по классификации видов толерантности с точки зрения различных наук. На основании анализа позиций различных авторов сделан вывод о том, что научные подходы к классификации толерантности в настоящее время отличаются большой пестротой, несогласованностью и достаточной противоречивостью. Поскольку критерии для обобщения такого обилия эмпирического материала пока не выработаны, целесообразной становится разработка единого методического инструментария, объединяющего в себе все перечисленные виды толерантности. The article is devoted to a theoretical review of scientific research on classification of kinds of tolerance from the point of view of various Sciences. The approaches to the problem in the context of various disciplines, such as cultural studies, political science, sociology, pedagogy, psychology, as psychology of intercultural communications, children and adolescents psychology, pedagogical psychology and psychology of a personality are being analyzed. The basic criteria underlying these classifications are studied. Based on the analysis of the above mentioned approaches of different authors we come to the conclusion that the scientific approaches to the classification of tolerance in the present time are rather contradictory and differ by great diversity and inconsistency. Since the criteria for generalization of such a plenty of empirical material have not been worked out yet, it becomes sensible to develop a unified methodological tools, which combines all of these kinds of tolerance.